2015
DOI: 10.1097/iio.0000000000000077
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Management of Acute Retinal Necrosis

Abstract: Acute retinal necrosis is a viral syndrome characterized by a panuveitis with necrotizing retinitis that may be complicated by retinal detachment, vaso-occlusion, optic neuropathy, and other causes of decreased visual acuity. Polymerase chain reaction testing provides a rapid and sensitive method of identifying the viral etiology of acute retinal necrosis, which is most commonly caused by herpes simplex virus type 1, herpes simplex virus type 2, and varicella zoster virus. Prompt diagnosis and treatment is par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 66 publications
0
50
1
3
Order By: Relevance
“…Adjunctive systemic corticosteroids were added only after stabilization of retinal lesions. The patient was then closely monitored for any exacerbation of intraocular inflammation or necrotizing retinitis [18]. The evolution was favorable with healing of retinitis lesions and gain of a normal visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…Adjunctive systemic corticosteroids were added only after stabilization of retinal lesions. The patient was then closely monitored for any exacerbation of intraocular inflammation or necrotizing retinitis [18]. The evolution was favorable with healing of retinitis lesions and gain of a normal visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the virus reaches the retina through neural pathways (Shukla et al 2009). ARN is characterized by a triad of panuveitis with occlusive vasculitis and necrotising retinitis Shantha et al 2015). The American Uveitis Society criteria for the diagnosis of ARN includes: one or more focus of peripheral retinal necrosis, rapid progression and circumferential spread of the disease without antiviral, evidence of occlusive vasculopathy with arteriolar involvement and a prominent inflammatory reaction in the vitreous and anterior chamber (Lauren et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the acute phase led to the development of proliferative retinopathy with the evidence of vitreous haemorrhage. Occlusive vasculitis and severe inflammation contributes to retinal hypoxia (Shantha et al 2015) which in turn, stimulates the production of vasoproliferative factors, leading to neovascularisation. Laser panretinal photocoagulation converts the ischaemic retina to an anoxic stage, thereby, removing the stimulus and promotes regression of neovascularisation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients receiving combination therapy showed a higher incidence of two-line-orgreater visual acuity and decreased incidence of RD and severe visual acuity loss to 20/200 or poorer when compared to patients who received systemic antiviral alone and similar results were obtained by Wong et al and Megphara et al They concluded that patients that with moderate disease (i.e., 25-50% retina involved) usually showed better results. However, Tibbetts et al found no statistically significant difference in the visual acuity and prevalence of retinal detachment with combination therapy [21].…”
Section: Treatmentmentioning
confidence: 97%